2019
DOI: 10.4103/jpn.jpn_61_18
|View full text |Cite
|
Sign up to set email alerts
|

Etiological profile of afebrile seizures in infants in a tertiary care center from southern India

Abstract: A bstract Introduction: Seizure is the most common neurological illness in pediatric population and its risk is highest in the first year of life. Studies regarding etiology of afebrile seizures worldwide and in India are limited; hence, the current study was undertaken. Objective: The objective of this work was to study the etiology of afebrile seizures in infants aged 1 month to 1 year. Materials and Methods: A re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
0
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 12 publications
0
0
0
2
Order By: Relevance
“…During the progression of the illness, autonomic disturbances such as sinus tachycardia, arterial hypotension, urine retention, significant xeroderma and hyperkeratosis, and hyperemia and hyperhidrosis may appear (Piradov et al 2001). The clinical manifestations of DP in children are not different from adults (Gowda et al 2022;Kanwal et al 2012;Manikyamba, Satyavani, and Deepa 2015).…”
Section: Treatmentmentioning
confidence: 86%
See 1 more Smart Citation
“…During the progression of the illness, autonomic disturbances such as sinus tachycardia, arterial hypotension, urine retention, significant xeroderma and hyperkeratosis, and hyperemia and hyperhidrosis may appear (Piradov et al 2001). The clinical manifestations of DP in children are not different from adults (Gowda et al 2022;Kanwal et al 2012;Manikyamba, Satyavani, and Deepa 2015).…”
Section: Treatmentmentioning
confidence: 86%
“…Despite the availability of effective vaccinations, diphtheria has the potential to resurface. Poor immunization coverage, interruption of the cold chain, inadequate living conditions, delayed reporting to the health center, and non-availability or delay in the administration of antitoxin are likely to contribute to the recurrence of the disease and higher mortality (Gowda et al 2022;Jammar et al 2021). The waning of immunity in adults is playing a part as a risk factor for this condition.…”
Section: Introductionmentioning
confidence: 99%
“…[7] In contrast to previous research, where the prevalence of MV, encompassing non-invasive ventilation, was 23%, our study's incidence of MV, including this kind of ventilation, was 11.5%. [8,9] The range of PICUs' mechanical ventilation rates for pediatric patients is between 14 and 60%. [10][11][12] According to one research, 52% of children in PICUs in Sri Lanka got MV, however, other studies revealed that the prevalence of MV was 30% and 34.6%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Le neuropaludisme et les méningites étaient les étiologies les plus fréquemment retrouvées dans cette zone [1,21,23]. Selon la littérature, les facteurs de risque significativement associés à la survenue d'une méningite sont l'âge inférieur à 12 mois, la léthargie, l'irritabilité, les vomissements, la raideur de la nuque, la fontanelle bombée, les maux de tête, la somnolence, le coma, les convulsions complexes et l'utilisation antérieure d'antibiotiques [14,24,25]. Selon la littérature occidentale, les convulsions fébriles représentent la majorité des crises observées chez les enfants de moins de 5 ans [9,13,14].…”
Section: IVunclassified
“…Selon la littérature, les facteurs de risque significativement associés à la survenue d'une méningite sont l'âge inférieur à 12 mois, la léthargie, l'irritabilité, les vomissements, la raideur de la nuque, la fontanelle bombée, les maux de tête, la somnolence, le coma, les convulsions complexes et l'utilisation antérieure d'antibiotiques [14,24,25]. Selon la littérature occidentale, les convulsions fébriles représentent la majorité des crises observées chez les enfants de moins de 5 ans [9,13,14]. La prise en charge des crises consistait aux urgences pédiatriques par la libération des voies aériennes et l'administration de diazepam.…”
Section: IVunclassified